UV Visible Spectrophotometric Approach and Absorption Model for the Discrimination of Diseased Blood - GUNASEKARAN, S.; NATARAJAN, R.K.; RENGANAYAKI, V. (Asian Journal of Chemistry, 2010)
In the present investigation, UV-visible spectral characteristics of the whole blood were studied for the classification of the patients with leukemia, anemia, liver cirrhosis, thalassemia and diabetes with reference to the healthy subjects. The optical density of the deseased blood was dramatically different from that of the healthy one. The optical densities and their ratios were used as input variables for the statistical analysis of normal and diseased blood. The observed differences were statistically significant and could be exploited to differentiate between the healthy and diseased blood.